Thermal stress analysis and characterization of thermo-mechanical properties of thin films on an elastic substrate - Hu, YingYong (2011)
Stress and thermomechanical behavior of thin films deposited atop a substrate upon thermal loading/unloading have been investigated extensively in the past decades, which was partially stimulated by the development of micro- and nanotechnology. However, most of the previous effort in analysis was focused on thin films in their linear elastic deformation range. On the other hand, either very dedicated equipments or complicated procedures were required for the determination of their properties.